Seismic Evaluation of High-Rise Building Performance During Earthquakes by Employing Shear Wall Framing Systems - Seyed Hakim, Seyed Jamalaldin; Zahri, Nur Izyanny; Mhaya, Akram; Jamaluddin, Norwati; Mokhatar, Shahrul Niza; Mohamad, Noridah; Abd Ghafar, Nor Hayati; Paknahad, Chia (International Journal of Integrated Engineering, 2024)
It is vital to consider earthquakes in high-rise building design due to the potential seismic hazards that can pose substantial dangers to the structural integrity and safety of these structures. These buildings are more prone to lateral forces and vibrations during an earthquake, given their height and mass. Incorporating seismic design measures, such as the use of shear walls, helps mitigate the effect of earthquakes on tall buildings, ensuring their resilience and the protection of human life and buildings. Designing structures exclusively for seismic protection may be economically impractical, given the rare occurrence of earthquakes during a structure's lifespan. Despite the infrequency of earthquakes in Malaysia, concerns among Malaysians have arisen due to seismic activities in neighbouring countries, prompting a need for considerations in constructing structures that address both economic feasibility and potential seismic threats. This research focuses on evaluating the seismic performance of a 50-story tall building during earthquakes, utilizing shear wall framing systems. Response spectrum analysis is applied to assess various parameters such as displacement, drift, and stiffness at different levels. The results of these parameters in a building with shear walls positioned at both the centre and corners are compared to those of a structure lacking shear walls. The study reveals that the placement of shear walls and the symmetry of the frame impact the building's performance during earthquakes. According to the findings, structures with shear walls demonstrate better resistance to deformation caused by seismic loads compared to buildings without shear walls. Therefore, integrating shear walls into tall buildings proves to be an advantageous strategy for mitigating seismic damage in high-rise structures. Therefore, incorporating shear walls into tall buildings proves to be a beneficial approach to mitigate seismic damage in high-rise structures.